THE ROLE AND EFFECTIVENESS OF ONLINE TEACHING IN CONTEMPORARY EDUCATION - Yakubova, Munisa (Scientific practical conference, 2026)
The rapid advancement of digital technologies has fundamentally transformed contemporary education systems worldwide. Online teaching, once regarded as a supplementary mode of instruction, has evolved into a core component of modern educational practice. This article provides a comprehensive analysis of the role and effectiveness of online teaching by examining its theoretical foundations, pedagogical advantages, practical challenges, and future prospects. Drawing on established educational theories, real instructional examples, and the perspectives of influential educational thinkers, the study highlights effective strategies that enhance learner engagement and academic achievement in virtual learning environments. The article argues that while online teaching offers significant benefits in terms of flexibility, accessibility, and innovation, its success largely depends on sound pedagogical design, teacher competence, and institutional support.